Continuous hydroxyalkylation of p-Cresol to 2,2 `-methylenebis(4-Methylphenol) in a fixed bed reactor - Garade, Ajit C.; Hengne, Amol M.; Deshpande, Tushar N.; Shaligram, Sayali V.; Shirai, Masayuki; Rode, Chandrashekhar V. (Journal of Chemical Engineering of Japan, 2009)
{Catalytic activity of various solid acid catalysts is evaluated for the continuous hydroxyalkylation of p-cresol to [